JENIS-JENIS BURUNG (AVES) YANG DIPERDAGANGKAN DI KAWASAN KAMPUNG PADANG KABUPATEN ROKAN HULU - Marwanti, Mei Dwi; Ade, Filza Yulina; Brahmana, Eti Meirina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about species of bird wich are traded in Rokan Hulu regency especially in Kampung Padang has been done in December 2014 with survey method. Samples were found than identified and described by using the reference guide book. Result showed 3 order, 11 families and 19 species of birds wich are traded in Rokan Hulu regency especially in Kampung Padang. The most traded is Passeriformes.